A walk to beautiful [videorecording (DVD)] - Smith, Mary Olive; Smith, Mary Olive; Bucher, Amy (WGBH Video, 2008)
A look at the lives of three Ethiopian women, rejected by their husbands and ostracized by their communities, who leave home in search of seeking treatment for obstetric fistula. The program follows them walking for hours on their journey to transportation to a special hospital in Addis Ababa where they find solace for the first time in years, and stays with them as their lives begin to change.